Integrative hypothesis for Huntington's disease: a brief review of experimental evidence - Perez-De La Cruz, V; Santamaria, A (Physiological research, 2007)
Huntington's disease (HD) is a demential, neurodegenerative inheritable disease affecting middle-aged patients. HD is characterized by uncontrolled choreiform movements, psychiatric symptoms and cognitive decline. Histopathological changes in HD brains reveal a considerable damage to basal ganglia, particularly affecting middle-sized spiny neurons from the caudate-putamen region. Neurochemical changes are specifically oriented to deplete GABAergic and cholinergic systems, while molecular alterations include an increased expression of CAG trinucleotide at exon 1 from the huntingtin (htt) gene, as well as aggregation of mutant htt. Although several hypotheses regarding the mechanisms by which neurotoxicity is triggered in HD brains have been suggested on the basis of experimental evidence, so far it remains not clear which of them are predominant or whether they are complementary. Recent experimental evidence through transgenic mice models reveal an interesting interaction between expanded CAG triplets, mutant htt, and the increase in toxic metabolites from the kynurenine pathway. Further evidence supports the assumption that different toxic mechanisms (i.e. excitotoxicity, energy metabolism impairment, inflammatory events, oxidative stress, etc.) are confluent and depend on each other. In this review we will briefly summarize some of those findings and propose a final integrative hypothesis for HD.
Keywords: buněčná smrt; kyselina chinolinová; Neurons; Tryptophan; trinukleotidové repetice; tryptofan; Excitatory Amino Acids; Inflammation; Kynurenic Acid; myši transgenní; zánět; vápník; Disease Models, Animal; kyselina kynurenová; membránové transportní proteiny pro serotonin; mutace; Energy Metabolism; Oxidative Stress; Mice; Serotonin Plasma Membrane Transport Proteins; Trinucleotide Repeats; Cell Death; Calcium; energetický metabolismus; Animals; modely nemocí na zvířatech; Mutation; zvířata; Humans; Propionates; neurony; excitační aminokyseliny; Huntington Disease; myši; propionáty; Quinolinic Acid; oxidační stres; Nitro Compounds; dusíkaté sloučeniny; Mice, Transgenic; lidé; Huntingtonova nemoc